2015
DOI: 10.7238/rusc.v12i3.1994
|View full text |Cite
|
Sign up to set email alerts
|

Digital literacy for teachers in Cuban Tourism and Hotel Management Schools. Some experiences on its development

Abstract: Digital literacy for teachers has been a widely studied topic in recent years, and several studies have been conducted featuring student-oriented ICT competency models and frameworks. This research aims to develop a teacher-oriented ICT Competency Framework for Cuban Tourism and Hotel Management School instructors, on the one hand, to have reference points or criteria to make an assessment on the actual status of ICT training and, on the other hand, to provide guidelines on ICT training for teachers. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The training of teachers' on technology needs to be continued by priorities to incorporate into the teaching profession (Avello Martínez and L opez Fernández, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The training of teachers' on technology needs to be continued by priorities to incorporate into the teaching profession (Avello Martínez and L opez Fernández, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This contradicts previous research that found specialization as a characteristic feature of research on literacy, and specifically on DL [9,[30][31][32]. To the results obtained in the SCOPUS database, it is necessary to add other investigations located in other databases that have served to build the theoretical framework and that contrast with the results presented because they focus on tourism, on teachers and are largely signed by the same authors [37][38][39].…”
Section: Discussionmentioning
confidence: 78%
“…From the above, it is understood that notable interest exists in academic research on the literacy of university students [1,19,31] characterized by a constant adaptation to the new demands derived from the changes experienced by the social environment, which are caused, to a large extent, by technological development [10,16,19,32]. Another feature that defines research on literacy, and specifically on DL, is its focus or specialization in specific areas or disciplines in response to the different levels of demand that professional sectors require of graduates [9,[33][34][35], including the tourist field [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations